2023
DOI: 10.3389/fphys.2023.1110802
|View full text |Cite
|
Sign up to set email alerts
|

Estimated power output for a distance run and maximal oxygen uptake in young adults

Abstract: Background: Both cardiopulmonary exercise testing (CPET) and run field tests are recommended by the American Heart Association for assessing the maximal oxygen uptake (VO2 max) of youth. Power output was highly correlated with VO2 max in CPET. However, it is unclear regarding the correlations of time and estimated power output (EPO) for a run field test with VO2 max obtained from CPET in young adults.Methods: This study included 45 participants, aged 20–40 years, from a sample of 1,120 military personnel who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Table 1 reveals the characteristics of total participants for the military exercise test (N = 1120) [ 28 ] and selected volunteers for both the muscular endurance tests and a CPET test (N = 45). [ 16 ] The characteristics of the volunteers for a CPET were similar to the overall sample, except older age was observed in those for a CPET. The mean age of military volunteers for a CPET was 29.93 ± 7.05 years, and more than 90% of the participants were males.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Table 1 reveals the characteristics of total participants for the military exercise test (N = 1120) [ 28 ] and selected volunteers for both the muscular endurance tests and a CPET test (N = 45). [ 16 ] The characteristics of the volunteers for a CPET were similar to the overall sample, except older age was observed in those for a CPET. The mean age of military volunteers for a CPET was 29.93 ± 7.05 years, and more than 90% of the participants were males.…”
Section: Resultsmentioning
confidence: 82%
“…Second, the internal validation for the accuracy in a normal weight sample (N = 35) against the 45 participants has been estimated up to 93.11%. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in patients with abdominal obesity and a high WHtR, the increase in intra-abdominal pressure due to chest expansion and diaphragm descent during inspiration may contribute to a decrease in CRF ( 30 ). Furthermore, a recent study has demonstrated that WHtR and waist circumference (WC) are more strongly associated with VO 2 max than BMI ( 31 ). Notably, it has been also suggested that the obesity paradox may be more pronounced in HF patients with low CRF ( 32 ).…”
Section: Discussionmentioning
confidence: 99%